Increased Production of Alcohol-Based Hand Rub Solution in Response to COVID-19 and Fire Hazard Potential: Preparedness of Public Hospitals in Addis Ababa, Ethiopia - Selam MN; Bayisa R; Ababu A; Abdella M; Diriba E; Wale M; Baye AM (Dove Medical Press, 2020)
Muluken Nigatu Selam,1 Regasa Bayisa,2 Andualem Ababu,2 Mahdi Abdella,2 Edessa Diriba,2 Minychel Wale,3 Assefa Mulu Baye4 1Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Pharmaceutical and Medical Equipment Directorate (PMED), Ministry of Health, Addis Ababa, Ethiopia; 3All African Leprosy, Tuberculosis Rehabilitation and Training Centre (ALERT), Addis Ababa, Ethiopia; 4Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Muluken Nigatu SelamDepartment of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, P.O. Box 1176, Addis Ababa, EthiopiaTel +251 912159807Email muluken.nigatu@aau.edu.etBackground: According to the World Health Organization (WHO), alcohol-based hand rubs (ABHRs) are regarded as the “gold standard” for hand disinfection in healthcare facilities. Local production of ABHRs in health facilities is recommended by WHO due to its availability and affordability reasons. However, fire hazard is a concern in health facilities during ABHRs production, storage, or use from dispensers.Objective: To evaluate the preparedness of public hospitals found in Addis Ababa, Ethiopia towards potential fire hazards during ABHR production and storage practices.Methods: A cross-sectional observational study was applied. An assessment checklist was used for evaluating public hospitals’ measures taken for the potential fire hazards during ABHR production and storage practice. Statistical Package for Social Sciences (SPSS) version 23 was used for data entry and analysis.Results: Out of the 13 public hospitals observed in the study, fire extinguishers were not available in more than half of the hospitals’ (7 hospitals) compounding premises. Also, 57.1% of the hospitals without fire extinguishers were manufacturing beyond the WHO 50 liters limit of ABHR solution at once under such unfavorable conditions. Moreover, ethanol and the oxidizing agent hydrogen peroxide were not stored separately in eight hospitals.Conclusion: None of the hospitals were found to be well prepared for the potential risk of fire associated with ABHR solution production and storage practice. Generally, the practices taken by the studied hospitals for preventing the fire risk and minimizing the damage if fire hazards occurred during ABHR production and storage were not satisfactory. On the safety and precautions measures taken for the risk of fire, Tikur Anbessa Specialized Hospital (TASH), Amanuel Mental Specialized Hospital (AMSH), and Eka Kotebe General Hospital (EKGH) showed a relatively better preparedness compared to others. ABHR solutions should be manufactured and stored in a way that limits the risk of ignition and follows standard fire safety measures.Keywords: ABHR, fire, hospitals, COVID-19, production, storage